CEPF Western Ghats Special Series: Rediscovery of the threatened Western Ghats endemic sisorid catfish Glyptothorax poonaensis (Teleostei: Siluriformes: Sisoridae) - N. Dahanukar (Journal of Threatened Taxa, 2011)
Glyptothorax poonaensis Hora is an endemic sisorid catfish of the Western Ghats of India known only from its type locality in Mula-Mutha River, a tributary of Bhima River, at Pune. This fish has not been recorded from its type locality for more than 70 years and it was thought to be extinct. Here we report a recently discovered population of G. poonaensis from Indrayani River, a tributary of Bhima River. Based on 11 specimens, we have redescribed this species along with some comments on its taxonomy, length-weight relationship, feeding and breeding habits. We also performed molecular phylogeny of the fish by sequencing three mitochondrial genes encoding 16S ribosomal DNA, cytochrome b and cytochrome oxidase subunit I. Molecular analysis suggests that G. poonaensis is nested within a lineage of Glyptothorax species from northern and northeastern India and China. Further, our analysis reveals that southern Indian species of Glyptothorax do not form a monophyletic group. Molecular dating of divergence times indicates that G. poonaensis diverged from other northern Indian species 1.9 to 2.5 million years ago. Current knowledge suggests that the species could be found in two river basins with total extent of around 6100km2; however, the species is already suspected to be locally extinct from half of its known extent of occurrence. Furthermore, the habitat of the species may be threatened by increasing pollution, deforestation leading to siltation, halting of flow by damming, sandmining and introduced fish species. In the light of biodiversity conservation, especially in an important biodiversity hotspot like Western Ghats, such rare and endemic species needs prioritization.